Intensity of space use reveals conditional sex‐specific effects of prey and conspecific density on home range size. Issue 9 (28th March 2016) - Aronsson, Malin; Low, Matthew; López‐Bao, José V.; Persson, Jens; Odden, John; Linnell, John D. C.; Andrén, Henrik
Abstract: Home range (HR) size variation is often linked to resource abundance, with sex differences expected to relate to sex‐specific fitness consequences. However, studies generally fail to disentangle the effects of the two main drivers of HR size variation, food and conspecific density, and rarely consider how their relative influence change over spatiotemporal scales. We used location data from 77 Eurasian lynx ( Lynx lynx ) from a 16‐year Scandinavian study to examine HR sizes variation relative to prey and conspecific density at different spatiotemporal scales. By varying the isopleth parameter (intensity of use) defining the HR, we show that sex‐specific effects were conditional on the spatial scale considered. Males had larger HRs than females in all seasons. Females' total HR size declined as prey and conspecific density increased, whereas males' total HR was only affected by conspecific density. However, as the intensity of use within the HR increased (from 90% to 50% isopleth), the relationship between prey density and area showed opposing patterns for females and males; for females, the prey density effect was reduced, while for males, prey became increasingly important. Thus, prey influenced the size of key regions within male HRs, despite total HR size being independent of prey density. Males reduced their HR size during the mating season, likely to remain close to individual females in estrous. Females reduced their HR size postreproduction probably because of movement constrains imposed by dependent young. Our findings highlight the importance of simultaneously considering resources and intraspecific interactions as HR size determinants. We show that sex‐specific demands influence the importance of prey and conspecific density on space use at different spatiotemporal scales. Thus, unless a gradient of space use intensity is examined, factors not related to total HR size might be disregarded despite their importance in determining size of key regions within the HR. Abstract : Since food and conspecific density are often strongly correlated in natural systems few studies have been able to simultaneously assess the effect of these two factors on individual spacing behavior. Using a long term and large scale location dataset from Eurasian lynx we show that sex‐specific needs influenced the importance of prey and conspecific density as home range (HR) size determinants. Furthermore, unless different spatiotemporal scales are examined, factors not related to total HR size might be disregarded as determinants of animal spatial ecology despite their importance for the size of key regions within the animal's HR.